Presence of candida in the dental plaque and saliva of patients with severe early childhood caries and early childhood caries: a pilot study - Esra Özgöçmen; Tuğba Yiğit; Hüseyin Haydar Kutlu (European Oral Research)
Purpose: The aim of this study is to evaluate the presence of candida, which is one of the etiological factors contributing to early childhood caries (ECC) and severe early childhood caries (S-ECC), in the dental plaque and saliva of children aged 6 years and younger.Materials and Methods: Our study involved 60 participants who met the inclusion criteria. Based on clinical examinations, we divided them into three groups, each consisting of 20 children: S-ECC, ECC, and caries-free groups. We collected dental plaque and saliva samples from the children during clinic visits. In the laboratory, we assessed these samples for the presence of candida using the Liofilchem® – ChromaticTM Candida (Roseto degli Abruzzi, Italy) medium and identified Candida species.Results: The presence of Candida in the saliva of children with S-ECC (40%) and ECC (30%) was statistically significant compared to children without caries (p<0.05). Observationally, we found a higher presence of candida only in the dental plaque of children with S-ECC (25%) and ECC (15%) compared to children without caries (p>0.05). In the S-ECC group, we detected Candida albicans, Candida glabrata, Candida krusei, and Candida tropicalis in saliva, while Candida albicans was found in dental plaque. In the ECC group, Candida albicans, Candida glabrata, and Candida krusei were detected, whereas Candida was not detected in children without caries.Conclusion: It is important to consider the presence of Candida in both saliva and dental plaque, as it potentially plays a role in the pathogenesis of ECC. These findings suggest that 3 This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record identifying and preventing Candida colonization may be valuable for individual risk assessment and could contribute to reducing ECC.